Новый импульсный модулятор с малой частотой переключений - Golub, V. S. (PE "Politekhperiodika", Book and Journal Publishers, 2014)
The author presents an integrating pulse modulator (analogue signal converter) with the pulse frequency and duration modulation similar to sigma-delta modulation (with low switching frequency), without quantization. The modulator is characterized by the absence of the quantization noise inherent in sigma-delta modulator, and a low switching frequency, unlike the pulse-frequency modulator. The modulator is recommended, in particular, to convert signals at the input of the class D power amplifier.